Temporal and spatial imaging of hydrogen storage materials: Watching solvent and hydrogen desorption from aluminium hydride by transmission electron microscopy - Beattie, S.; Humphries, Terry; Weaver, L.; Sean McGrady, G. (The Royal Society of Chemistry, 2008)
An in situ thermal desorption study of solvated aluminum hydride (alane) by transmission electron microscopy and selected area diffraction has permitted characterisation of the structural and morphological changes during desorption of solvent and hydrogen in real-time; this powerful technique for studying hydrogen storage materials complements several others already employed. © The Royal Society of Chemistry.